Looking to the future of visual assessment using driving simulation - Wilkie, Richard McGilchrist; Mole, Callum David (Scandinavian Journal of Optometry and Visual Science, 2017)
Visual function is considered uniquely important for driving because it provides multiple critical sources of information that when combined ensures successful steering. There are, however, additional cognitive functions that are essential for the driver to be able to dynamically respond to the world and make predictions about the scene, as well as the behaviour of other road users. Given the complexity of driving through a busy urban environment it should be no surprise that simple tests of visual acuity seem to have weak explanatory power in terms of increased crash risk when driving. Despite this, fitness to drive still includes a formal assessment of visual acuity, with poor scores being used to revoke the driving licence. The ’gold standard’ measure of driving ability remains the on-road driving test but compared to visual tests they are fairly uncontrolled, susceptible to great variation depending on the road conditions, and are unable to reliably detect subtle visual deficits. To address some of the limitations of these existing tests we use examples from two simulator settings (steering control and hazard detection) that highlight the merits of using driving simulation in order to control the visual conditions and probe specific functional capabilities of drivers. When used in conjunction with visual tests these methods will not only determine whether the core functions of driving are intact but also be able to provide richer feedback to individuals about the nature of their deficits. There are many exciting possibilities using simulation techniques to establish predictive relationships between routine visual testing and driving performance, ultimately aiming for better, more reliable assessment of fitness to drive.